2009
DOI: 10.1177/0886260509336960
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Against Married Women in Edirne

Abstract: The aim of this study is to assess the prevalence and risk factors of domestic violence against married women in Edirne, Turkey. This is a cross-sectional study which included a representative sample of the married women living in the Provincial Center of Edirne. The total past year prevalence of some forms of physical domestic violence is 34% in the last 12 months. 93% of women reported that they have been experiencing different forms of verbal and psychological domestic violence. The important risk factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0
18

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 29 publications
6
55
0
18
Order By: Relevance
“…A study conducted in a primary care unit in the city of Porto Alegre, southern Brazil, found a 38% prevalence of IPV. 12 Schraiber et al 15 investigated users of 19 primary care services in the metropolitan area of São Paulo, and found a 40.4% prevalence of IPV, ranging from 38.6% to 42.1%. Marinheiro et al, 13 in a study limited to one health district in Ribeirão Preto, estimated an IPV prevalence of 26.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in a primary care unit in the city of Porto Alegre, southern Brazil, found a 38% prevalence of IPV. 12 Schraiber et al 15 investigated users of 19 primary care services in the metropolitan area of São Paulo, and found a 40.4% prevalence of IPV, ranging from 38.6% to 42.1%. Marinheiro et al, 13 in a study limited to one health district in Ribeirão Preto, estimated an IPV prevalence of 26.4%.…”
Section: Discussionmentioning
confidence: 99%
“…2,18 In developing countries like Turkey, IPV is associated with poverty, unemployment, low education, large number of children and female submission to family authority. 15 Being the head of household opposes social norms of gender roles and can promote IPV. In emerging economy countries, women who become more socially powerful may face an increased risk of IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Entre los factores comunitarios encontrados destacan la falta de poder de las mujeres (Kishor y Johnson, 2004;Tokuç, Ekuklu y Avcioğlu, 2010), el contexto cultural y la globalización (véase Tabla 1 con los datos del meta-análisis realizado por Stith et al en el año 2004 y de los estudios individuales).…”
Section: Factores De Riesgo Asociados Al Macrosistemaunclassified
“…Wife abuse occurs in different forms such as physical, sexual, psychological, fiscal, and social (Ezazi, 2002;Hegarty, Hindmarsh, & Gelles, 2000;Records, 2007). Wife abuse is a social problem in the world (Alio, Nana, & Salihu, 2009;Tokuc, Ekuklu, & Avcioglu, 2010); for instance, there were over 102,500 victims of intimate abuse in Canada in 2010 (Sinha, 2012). Nagae and Dancy (2010) reported physical, psychological and sexual abuse among women in Japan.…”
Section: Introductionmentioning
confidence: 99%